Geological and geomorphological evidence of holocene activity along the maisu fault in the northern Sichuan–Yunnan block, Tibetan Plateau - Zuo, Hong; Qin, Yulong; Liang, Mingjian; Sun, Kai; Huang, Feipeng; Liao, Cheng; Zhou, Wenying; Wu, Weiwei; Zhang, Huiping; Yang, Yao (Frontiers in Earth Science, 2022)
The Sichuan–Yunnan block is located in the eastern of Tibetan Plateau and exhibits strong tectonic and earthquake activity. The Maisu fault is an E–W-trending fault within this block. Via interpretations of remote-sensing imagery and field surveys, we identified a earthquake surface rupture zone that has developed along the Maisu fault; we then estimated its Holocene activity. The surface rupture extends westward from the town of Puma, Sichuan Province, to the village of Worilong, Xizang Province, and has a length of approximately 45 km. According to a fault outcrop and carbon-14 dating of a profile near the village of Yongqu, Xizang Province, the most recent earthquake along this rupture may have occurred after 1850 ± 30 BP. The Maisu fault extends eastward and may intersect the Garzê–Yushu fault. Accordingly, as a secondary fault, the Maisu fault likely accommodates the partitioned horizontal slip deformation of the Garzê–Yushu fault.